Psychometric development of an independence scale for students with mild intellectual disabilities - Andi Prabowo; Edi Istiyono; Farida Agus Setiawati (Jurnal Penelitian Ilmu Pendidikan, 2024)
Measuring the independence of students with mild intellectual disabilities requires a well-validated and culturally appropriate instrument as a foundation for designing effective educational interventions. However, in Indonesia, such tools remain limited. This study aimed to develop a non-cognitive Independence Scale for students with mild intellectual disabilities and to evaluate its psychometric properties, including validity, reliability, item difficulty, and discrimination. A 30-item Likert-scale instrument, rated by teachers, was constructed to measure three domains: Personal, Social, and Academic Independence. The scale was pilot tested on 100 students with mild intellectual disabilities at SLB Negeri Manggar. Quantitative analyses using R Studio included tests of item validity (corrected item–total correlations), internal consistency (Cronbach’s α), item discrimination (upper–lower group method), item difficulty indices, and normality of total scores (Shapiro–Wilk and Kolmogorov–Smirnov tests). All 30 items demonstrated acceptable validity (r ≥ 0.39) and high internal consistency (Cronbach’s α = 0.919). Item discrimination indices were satisfactory (D ≥ 0.30). Seventeen items (57%) were categorized as “Easy” (p > 0.70), while the rest showed moderate difficulty levels, and no items were too difficult (p < 0.30). The total scores were normally distributed (p > 0.05). Overall, the Independence Scale exhibited strong psychometric properties, indicating its suitability for assessing the independence of students. Future revisions are recommended to refine items that were identified as Easy to enhance discrimination among higher-performing students.